(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2024)
This study describes an influence of zirconia addition on some porcelain properties, particularly mechanical properties such as hardness and strength, depending on results of some previous researches which describe the methods of porcelain strengthening and toughening due to use the porcelain in many applications in daily life, such as dental porcelain, electrical porcelain and sanitary ware from porcelain. Porcelain has very important properties which make it a suitable material to other promised applications. For this reason, it must be defined the last information to which the recent researches reached to benefit from those methods in an improving of the porcelain properties to use it in suitable applications. This study showed that it can be significantly benefited from the zirconia addition to porcelain in an improving of many properties for it.